Doctors and nurses training needs for children's palliative care. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Downing, Julia; Boucher, Sue; Marston, Joan
Abstract : Objectives: Children's palliative care (CPC) represents a special, albeit closely related, field to adult palliative care and in many parts of the world, training on CPC is minimal or non-existent. Thus the ICPCN undertook a survey to understand training needs for CPC. Method: An online survey was developed addressing training needs alongside availability of CPC training programmes. The survey was online for four months from April 2011 and all ICPCN members were invited to participate. Results: Of the 253 respondents, 72 (28%) were doctors and 96 (38%) nurses. Doctors were most knowledgeable, on a scale of 1-5, in pain assessment and management (x=4.17) and the basics of CPC (x =4.15) and least knowledgeable about HIV/AIDS (x=2.83), dermatology (x=3.19) and development of CPC services (x=3.19). They felt most confident in communicating with children (x=3.93) and working with families (x=3.93) and least confident in HIV/AIDS (x=2.79) and therapies such as play (x=2.78). They prioritised their training needs as communicating with children, psychological aspects and setting up and managing services. Their least priority included feeding and hydration, cancer and dermatological issues. Nurses felt most knowledgeable in working with families (x=4.02) and self care (x=3.9), and least knowledgeable about HIV/AIDS (x=2.91) and Ethics and the Law (x=3.02). However they felt most confident about communicating with children (x=3.88) and working with families (x=3.92) and least confident about HIV/AIDS (x=2.79) and Dermatological issues (x=3.15). They prioritised Ethics and the Law, Neurological symptoms and setting up and managing services, with basics of CPC, communication and gastrointestinal symptoms being seen as least priority in terms of training needs. Conclusion: Further analysis is on-going to assess how priorities differ according to the regions in which respondents live, however understanding the training needs of doctors and nurses in CPC will help shape the development of an international training strategy within ICPCN.